Anthropometric and physiological correlates of 20 m sprint in elite young female handball players: The effect of change of direction - Kostoulas, I. D.; Tasiopoulos, I.; Fernandez-Garcia, A. I.; Nikolaidis, P. T. (21st Annual Congress of the European College of Sport Science (ECSS), Vienna, 6. -9. July 2016, 2016)
Introduction: The role of anthropometric and physiological characteristics for sprint in handball has been well documented (1-3); however, less information is available about correlates of sprint with change of direction (COD). The aim of the present study was to examine anthropometric and physiological correlates of 20 m sprint in-line (IL) and with COD in elite young female handball players. Methods: Twenty-two femle handball players (experience 3.8 (1.6) yrs, age 16.5 (0.7) yrs, height 166 (8) cm, weight 64.1 (11.8) kg, body mass index, BMI, 23.1 (3.3) kg.m-2) performed a series of anthropometric (height and weight) and physiological measures (sit-and-reach test, SAR, right and left handgrip muscle strength test, HGT, Abalakov jump test, AJ, standing broad jump, SBJ, 20 m sprint IL and 20 m sprint with COD). Results: Sprint with COD (5.07 (0.41) s) correlated with weight (r=0.44, p=0.042) and BMI (r=0.50, p=0.017). Both sprint IL and COD correlated with HGT (r=-0.65 and r=-0.70, p<0.001, respectively), AJ (r=-0.81, p<0.001 for both) and SBJ (r=-0.74 and r=-0.77, p<0.001, respectively). A step-wise regression analysis revealed that (a) 20 m sprint IL could be predicted by the equation: 20 m sprint IL = 4.702 - 0.037 × AJ (R2=0.65, SEE=0.15); (b) 20 m sprint with COD could be predicted by the equation: 20 m sprint with COD = 6.820 - 0.061 × AJ (R2=0.65, SEE=0.25). Conclusions: Based on these findings, it was concluded that an excess body weight might have larger impact on sprint with COD than IL. The observation that both sprint modes could be predicted by AJ highlighted the importance of lower limb muscle power for sprint ability either IL or with COD.